2012
DOI: 10.1001/archsurg.2012.1660
|View full text |Cite
|
Sign up to set email alerts
|

Selective Preoperative Magnetic Resonance Imaging in Women With Breast Cancer

Abstract: The use of preoperative magnetic resonance (MR) imaging may have an effect on the reoperation rate in women with operable breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…The majority of these reports showed no differences 3,10,11,13,15,16 , except for one by Mann et al where a significantly lower rate of re-excision at 5% was seen for patients who received pMRI in comparison to 15% for those who did not. 12 Two recent European randomized trials evaluated the efficacy of pMRI among BC patients.…”
Section: Discussionmentioning
confidence: 94%
“…The majority of these reports showed no differences 3,10,11,13,15,16 , except for one by Mann et al where a significantly lower rate of re-excision at 5% was seen for patients who received pMRI in comparison to 15% for those who did not. 12 Two recent European randomized trials evaluated the efficacy of pMRI among BC patients.…”
Section: Discussionmentioning
confidence: 94%
“…Two of the eligible studies were based on young women 15;16 and another 2 studies 14;26 were based on older women from overlapping datasets (SEER Medicare data in women aged 66 years and older); only one of the 2 overlapping studies was included in each analysis (online Appendix-1 provides additional details). Most studies specified that patients who received neoadjuvant therapy were excluded 14;16;21;22;25;27;3034 (only one study included patients who had neoadjuvant therapy 15 ). Two studies excluded patients with BRCA gene mutations 23;31 , otherwise this information was not explicitly reported.…”
Section: Resultsmentioning
confidence: 99%
“…We did not correlate our findings with any outcome measure such as re‐excision rates or local recurrence. However, many studies including a randomized clinical trial have not shown that MRI affects re‐excision rates, or recurrence rates . A meta‐analysis of over 3,000 patients also did not show that preoperative MRI reduced risk of local or distant recurrence compared to patients who did not get MRI .…”
Section: Discussionmentioning
confidence: 95%